Innovative procedures for micro‐elimination of HCV infection in persons who use drugs. Issue 12 (13th September 2020) - Messina, Vincenzo; Russo, Antonio; Parente, Enrico; Russo, Giovanni; Raimondo, Tiziana; Salzillo, Angela; Simeone, Filomena; Onorato, Lorenzo; Di Caprio, Giovanni; Pisaturo, Mariantonietta; Coppola, Nicola
Abstract: People who use drugs are a key population in global HCV control. We evaluated the efficacy of an innovative model to eliminate HCV infection in a high‐risk population of PWUD in a service for substance use disorder (SUD). Between January 2018 and December 2018, we conducted a prospective, interventional, before and after study, based on audits performed by Infectious Diseases physicians in a SUD facility in Piedimonte Matese, in southern Italy, to improve the knowledge about HCV infection; a shared protocol for screening and linkage to care of patients was implemented. The pre‐intervention period was defined as January‐December 2017 and the post‐intervention period as January‐December 2018. The subjects followed up at SUD facility in the pre‐intervention and post‐intervention periods were 318 and 275, respectively. Compared with the pre‐intervention period, the number of anti‐HCV–positive subjects tested for HCV RNA was higher in the post‐intervention period (91% vs 27%, P < .0001), as was the number who started directly acting antivirals (DAAs). Of the 18 HCV RNA–positive subjects in the pre‐intervention period, only 3 (16.6%) started DAA, a percentage decisively lower than that observed after the start of the programme, 63 (84%) of 75 subjects ( P < .0001), and all obtained SVR. The data were similar for people who inject drugs (PWID) and non‐PWID sub‐populations. The use of our innovative model with close interaction between the Infectious Disease Unit and the SUD facility determined a significant increase in HCV RNA testing, linkage to care and the start of DAA in the PWUD population.